Appropriation, réemploi et transfert. Du concours de l’image dans la traduction de Travels through the Interior Parts of America de Thomas Anburey - Marie-Lise Poirier; Peggy Davis; Marjorie Charbonneau (Viatica)
This analysis of Thomas Anburey’s Travels through the Interior Parts of America is based on different editions and translations published between 1789 and 1793. The translations’ editorial choices can modify the understanding, the reception, or the reading experience of the book (expanded edition annotated by the translator or changes made to the iconographic program). Based on the materiality of the book, the comparative analysis enables to reveal these differences and to account for the relationship between image and text. Here, the engraving An Indian Warrior from the original edition is analyzed with regard to its French and German translations, in order to demonstrate the need to consider the contribution of the engraved and printed image in geographical translation and compilation operations.